Question
16. \( (\sqrt{6})(-\sqrt{24})= \)
Ask by Fowler Lindsey. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\(-12\)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
First, let's simplify the expression \( (\sqrt{6})(-\sqrt{24}) \). The square root of 24 can be simplified as follows: \( \sqrt{24} = \sqrt{4 \cdot 6} = \sqrt{4} \cdot \sqrt{6} = 2\sqrt{6} \). Now, substitute this back into the expression: \[ (\sqrt{6})(-\sqrt{24}) = (\sqrt{6})(-2\sqrt{6}) = -2(\sqrt{6} \cdot \sqrt{6}) = -2 \cdot 6 = -12. \] So, the final result is \(-12\).